2016
DOI: 10.1111/aji.12610
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in combination with trehalose has supplementary beneficial effects on cryopreserved red deer (cervus elaphus) sperm

Abstract: Therefore, glutathione in combination with trehalose could be a promising cryoprotectant for red deer sperm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Ansari et al (2014) observed that the addition of 0.5mM glutathione in semen extender improved the motility, plasma membrane integrity, viability and acrosomal integrity of Sahiwal bull spermatozoa. These results are in agreement with Wang and Dong (2017) who reported that glutathione addition to the extender improved sperm quality, including sperm motility, acrosomal integrity, plasma-membrane integrity and sperm morphology. Similarly, Gadea et al (2005) reported beneficial effect of GSH in cryopreserved boar spermatozoa in terms of acrosomal intactness and percentage of non-capacitated spermatozoa, corroborated the findings of this study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Ansari et al (2014) observed that the addition of 0.5mM glutathione in semen extender improved the motility, plasma membrane integrity, viability and acrosomal integrity of Sahiwal bull spermatozoa. These results are in agreement with Wang and Dong (2017) who reported that glutathione addition to the extender improved sperm quality, including sperm motility, acrosomal integrity, plasma-membrane integrity and sperm morphology. Similarly, Gadea et al (2005) reported beneficial effect of GSH in cryopreserved boar spermatozoa in terms of acrosomal intactness and percentage of non-capacitated spermatozoa, corroborated the findings of this study.…”
Section: Resultssupporting
confidence: 93%
“…Glutahione was reported to be used as a cryoprotectant for the sperm of mouse, canine, boar, ovine, bull and red deer (Sławeta & Laskowska, 1987, Takeo & Nakagata 2011, Perez et al, 2012, Anel-López et al, 2015and Lucio et al, 2016. Recently, Wang and Dong (2017) reported that glutathione addition to the extender improved sperm quality, including sperm motility, acrosomal integrity, plasma-membrane integrity and sperm morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of available studies show coherent results, even though there are contradictory ones demonstrating higher concentrations of GSH in patients with azoospermia compared to oligozoospermia or normozoospermia [ 49 ]. Several studies demonstrated that the addition of GSH to cryopreserved ejaculate of animals protects the sperm from the harmful effects of ROS accumulated during this process, at the same time improving sperm motility, viability, the integrity of the cell membrane, and sperm DNA, as well as the activity of antioxidant enzymes [ 50 , 51 , 52 ]. The addition of cysteine to rabbit ejaculate increased biosynthesis of intracellular glutathione and significantly affected cell membrane integrity, acrosomal inviolability or sperm motility [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose (Tre) is a stabilizer of the lipid membrane, protein, and biofilm system. During the cryopreservation of sperm cells, it acts as a protective agent to reduce the formation of intracellular ice crystals, to maintain protein structure, and significantly improve the mobility of sperm cells, as well as acrosome and cell membrane stability, reducing sperm cell aberrations or lesions (Wang and Dong, 2017). The addition of antioxidants to the cryoprotectant contributes to the protection of sperm cells from the adverse effects of reactive oxygen species and improves sperm cell recovery survival.…”
Section: Introductionmentioning
confidence: 99%